A FORECASTING OF THE NEELAM PERFUM PRODUCTION USING THE SARIMA METHOD TO MEET THE EXPORT DEMAND (CASE STUDY: ARC USK) - Raihan Dara Lufika; Syahriza Syahriza; Didi Asmadi; Edy Fradinata; Friesca Erwan; Riski Arifin; Longga Nabila (Universitas Putera Batam, 2022)
The rapid development of industry in Indonesia has resulted in many companies and business actors starting to contribute to international market competition. Planning for finished product requirements is one of the important points for companies in making strategies in the business world so that companies are able to compete in the market. ARC USK is one of the leading research centers in Aceh that has produced commercial patchouli products, one of which is the Neelam Parfum product. The problem faced by ARC USK at this time is that the need for the amount of export production of Neelam Parfum itself cannot be determined with certainty, this is because ARC USK has never exported Neelam Parfum products and so far only distributes it domestically so that the amount of commercial production is only made for meet the needs of the domestic market. This study aims to create an export production schedule for Neelam Parfum using the SARIMA method and determine an implementation strategy to maximize production activities for Neelam Parfum ARC USK. Data processing is carried out using data on the number of Neelam Parfum export production targets for 2020-2021 with the help of the Eviews10 software. The validation process for forecasting is carried out using MAPE calculations. The results showed that the MAPE value was 21.334%, based on these results the forecasting of 12 periods in 2022 using the selected SARIMA model can be used and there are 9 implementation strategies that have been approved by ARC USK for export production activities of Neelam Parfum.